The Electrical Characteristic Analysis of Reduced Graphene Oxide in Pt-Free DSSC Using Single Diode Model and Electrochemical Impedance Spectroscopy - Aprilia, Annisa; Yuliasari, Fitri; Siregar, R.E; Syakir, Norman; Bahtiar, Ayi; Safriani, Lusi; Hidayat, Sahrul; Hanipah, Iip; Fitrilawati, Fitrilawati (Fakultas Matematika dan Ilmu Pengetahuan Alam, Univetsitas Tanjungpura, 2022)
We studied the characteristic of reduced graphene oxide (rGO) as a counter electrode (CE) in Pt-free dye-sensitized solar cell (DSSC) using single diode model equation based on current density-voltage (J-V) measurement. The electrical characteristics of DSSC was investigated by electrochemical impedance spectroscopy (EIS) in order to knowing the catalytic properties of rGO as counter electrode. The rGO thin film as CE was deposited on fluorine-doped tin oxide (FTO) substrate and stacked with FTO/TiO2/ruthenium dye/mosalyte/rGO/FTO DSSC structure. The rGO film was obtained from GO (graphene oxide) film that was thermally reduced at 200°C for one hour under argon flow. The performance of DSSC with rGO as CE was characterized by current-voltage measurement and the interface between each layer was observed by Electrochemical Impedance Spectroscopy (EIS). The device efficiency (η) of DSSC that used GO and rGO film as CE are 0.09% and 3.43%, respectively. DSSC parameters such as series resistance (RS) shunt resistance (RSH), and ideality factor (n) were obtained from J-V curve which analyzed using single diode model equation. All samples have a Rs value of 2 indicates that all devices have a good ohmic contact. The RSH of device using rGO-1mg/ml is increase (from 2850 to 3670 Ω.cm2) compared with GO indicate that thermal reduction is successes. The rGO film shows a comparable performance to Pt-conventional CE thus it is a good candidate as alternative of DSSC counter electrode.